2012
DOI: 10.1182/blood-2011-07-368720
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate, an endogenous TLR4 agonist, promotes acute GVHD after allogeneic stem cell transplantation

Abstract: Graft-versus-host disease (GVHD) remains the most common cause of nonrelapse-related morbidity and mortality after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Although T-cell depletion and intensive immunosuppression are effective in the control of GVHD, they are often associated with higher rates of infection and tumor recurrence. In this study, we showed that heparan sulfate (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 48 publications
4
84
0
Order By: Relevance
“…However, recent experimental studies suggests a role for DAMPs such as ATP, heparan sulfate (HS), and uric acid, in enhancing allogeneic T-cell responses and in exacerbating GVHD. 15,17,32 Clinically, the data also suggests that response to DAMPs such as HMGB-1, 35 heat shock protein 70 (HSP70), 36,37 and HSP90 38 may be associated with GVHD severity in humans. In line with this notion, several pattern recognition receptors that are known to activate innate immunity in response to DAMP-mediated stimulation of APCs have been shown to exacerbate GVHD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, recent experimental studies suggests a role for DAMPs such as ATP, heparan sulfate (HS), and uric acid, in enhancing allogeneic T-cell responses and in exacerbating GVHD. 15,17,32 Clinically, the data also suggests that response to DAMPs such as HMGB-1, 35 heat shock protein 70 (HSP70), 36,37 and HSP90 38 may be associated with GVHD severity in humans. In line with this notion, several pattern recognition receptors that are known to activate innate immunity in response to DAMP-mediated stimulation of APCs have been shown to exacerbate GVHD.…”
Section: Discussionmentioning
confidence: 98%
“…[12][13][14] Recent experimental data have demonstrated that targeting certain DAMPs and the activation of APCs induced by them, can lead to aggravation of acute GVHD. [15][16][17] Alloreactive donor T lymphocytes, activated by both donor and host APCs, are absolutely critical for induction and perpetuation of GVHD. 7 Activation of the innate immune system, such as the APCs, plays a key role in enhancing the severity of donor T-cell-mediated GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…Our observations indicate that higher levels of AAT in donor plasma were associated with a reduced GVHD risk in the respective recipients. Along with data in murine models, [7][8][9] these observations suggest that AAT levels might serve as a biomarker with predictive value for GVHD. However, AAT levels vary widely between individuals under steady state conditions, although they rise significantly during inflammation or infections.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] AAT is a serine protease inhibitor, which in addition to changes in cytokine profiles, also affects the redox status of cells and cell-mediated immunity, among other functions. 6,[10][11][12][13][14][15] Taken together, available data indicate that AAT therapy is beneficial in a broad spectrum of inflammatory and immune-mediated diseases not related to genetic AAT deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the best-known ligand LPS, TLR4 can be activated by endogenous ligands, such as the extracellular matrix component heparan sulfate. 25 Developing B cells are positioned in specific cellular niches in the bone marrow that supply the microenvironment that is essential for their differentiation. 26 Endogenous ligands of TLR4 can be a part of the network modulating B lymphopoiesis.…”
Section: Synergism Of Lps and Il-7 Signals In The Promotion Of Pre-bcmentioning
confidence: 99%